2019
DOI: 10.1002/poi3.211
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Political Activity in the Formation of Online Identity Bubbles

Abstract: Increasing social media use has transformed political participation by creating social cliques and echo chambers, which involve interaction between like‐minded people. This article examines the relationship between online political activity and personal involvement in online identity bubbles. This study is the first to examine this phenomenon using nationally representative data; its data were derived from surveys targeted at 18–74‐year‐old Finns (N = 3,724). Measures included online political activity, the Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 62 publications
0
13
0
2
Order By: Relevance
“…Due to this difference from the U.S., more research is needed to understand the contextual and cultural differences potentially explaining these results. For example, scholarship on online cliques and bubbles has shown that they vary culturally and topically (Keipi et al, 2017;Koivula et al, 2019). Additionally, negative peer influence on deviant behavior has been widely demonstrated (Cutrín et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this difference from the U.S., more research is needed to understand the contextual and cultural differences potentially explaining these results. For example, scholarship on online cliques and bubbles has shown that they vary culturally and topically (Keipi et al, 2017;Koivula et al, 2019). Additionally, negative peer influence on deviant behavior has been widely demonstrated (Cutrín et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly the case on the Internet, where it is very easy to get access to harmful and deviant content and form social contacts with like-minded peers (Keipi et al, 2017;Oksanen et al, 2016;Oksanen et al, 2014). Negative influences gained online might be enforced by "social cliques" or "social bubbles" of other similar people (Kaakinen, Sirola, et al, 2018;Keipi et al, 2017;Koivula et al, 2019;Savolainen et al, 2020). However, strong ties with offline friends have been shown to buffer risky online behavior (Kaakinen, Keipi, et al, 2018).…”
Section: Social Bondsmentioning
confidence: 99%
“…В статье финских коллег [72] на основе модели усиления идентичности пузыря социальных сетей [51] показано, как личное и профессиональное использование социальных сетей связано с кибербуллингом и виктимизацией на рабочем месте, как вовлечение в социальные сети смягчает взаимосвязь этих явлений с такими проблемами как психологический стресс, техностресс и профессиональное выгорание. В связи с этим следует подчеркнуть, что пузыри идентичности определяют деятельность людей [52] и связаны с процессами социальной идентификации [105].…”
Section: предикторы кибербуллингаunclassified
“…To gain a more detailed understanding of how political motivators associate with different behaviors, we assess how the relations between behaviors and politically active social media use as well party preference overlap. Recent research shows that politically active social media users tend to support more extreme political values (Koiranen, Koivula, Saarinen, & Keipi, 2020a) and are more likely to become entangled in identity bubbles (Koivula, Kaakinen, Oksanen, & Räsänen, 2019a). In this respect, politically active social media use may encourage supporters of different parties to leverage different online behaviors.…”
Section: Introductionmentioning
confidence: 99%